Permanências e mudanças da educação rural e da educação campo no município de Salto do Lontra: 1998 a 2022 - Wessling, Elizangela (2023)
This thesis is linked to the research line Society, Knowledge and Education of the Stricto Sensu Post-Graduate Program in Education, master’s level of the Western Paraná State University – Unioeste, Campus of Francisco Beltrão. It discusses issues related to Field Education, which aim to actualize fundamental rights to subjects living in/of the rural area through a quality education that guarantees the appropriation of scientific, philosophical and artistic knowledge, enabling interpretation and intervention in reality, taking into account the rural area as a space that produces culture and knowledge. It is known that, historically, this right has been denied to peasants, since many schools, until today, have not yet surpassed the school practices of the “old” Rural Education. Therefore, this investigation sought to analyze the permanence and changes of Rural Education and Field Education in the county of Salto do Lontra/PR between the years 1998 to 2022. To answer the central question of the research, the work was divided into four chapters. The first chapter discusses the history of Rural Education and Field Education in Brazil from 1889 to 2022 in its determining notes. The second chapter sought to analyze Rural Education and Field Education in Paraná, in the Southwest and in Salto do Lontra. The third chapter sought to examine public policies from 1998 to 2022 and the possibility of overcoming Rural Education by Field Education. And the fourth, and last chapter, aimed to identify and analyze the permanence and changes in Rural Education and Field Education in the county of Salto do Lontrabetween the years 1998 to 2022. For the development of the work, a qualitative research was carried out, in which semi-structured interviews were conducted with the pedagogical teams of primary and secondary public field schools. The documents of the closure and nucleation process of rural schools, the Municipal Education Plans of 2007 and 2015 were analyzed, as well as the Pedagogical Political Projects of the eight public field schools that attended students in 2022. With the documents analyzed, it was found that, in the 1980s, there were 58 rural schools in Salto do Lontra. At that time, most of the communities in the county had a school. However, especially since the 1990s, there has been the closure and nucleation of several schools, with students being transferred to another public rural/field school during this period. With the Municipal Education Plan of 2015, it was possible to verify that in Salto do Lontra there is both the presence of rural schools and field schools, since the document presents goals for these two conceptions of schools. In general, therefore, the hypothesis of the research is confirmed, that there are permanences and changes in Rural Education and Field Education in Salto do Lontra. With this research, it was found that in Salto do Lontra there is a dialectical relationship between the permanence of Rural Education and the changes in Field Education, because the historical movement that involves them intertwines.